The Influence of Structure Height and Use of Shear Walls on the Behavior of Reinforced Concrete Building Structures - Muhammad Fauzan Hanif; Rosidawani Rosidawani; Siti Aisyah Nurjannah; Hanafiah Hanafiah (Jurnal Indonesia Sosial Teknologi, 2024)
Bengkulu is one of the areas prone to earthquakes. The application of earthquake-resistant reinforced concrete buildings must be done to minimise lateral forces due to earthquakes. The reinforced concrete structure system commonly used to withstand these lateral forces is a double system using sliding walls. Shear walls are structural elements that can affect rigidity and withstand lateral loads due to earthquakes. In addition, the structure's height will affect the load acting on the structure and the dimensions of the planned structural elements. This study aims to analyse the influence of structural height and the use of sliding walls on the behaviour of reinforced concrete building structures. The analysis in this study used spectrum response method analysis with the help of the ETABS application. Results show that the use of shear walls makes the structure stiffer at lower levels, and the higher the structure will result in the period of the structure, the primary shear force, the deviation between levels, and the influence of P-delta increases.